The Association between Parental Occupation, Family Income, and Availability of Sanitary Latrines with Stunting among Under-Five Children in the Working Area of Batu Bua Primary Health Center, Murung Raya Regency, 2025: HUBUNGAN JENIS PEKERJAAN ORANG TUA, PENDAPATAN KELUARGA DAN KETERSEDIAAN JAMBAN SEHAT DENGAN KEJADIAN STUNTING PADA BALITA DI WILAYAH KERJA PUSKESMAS BATU BUA, KABUPATEN MURUNG RAYA TAHUN 2025 - Sinaga, Joshua Doni Raja Dapot (Barigas: Medical and Health Science Journal, 2026)
Stunting remains a major public health issue in Indonesia, including Murung Raya Regency, Central Kalimantan Province. This study aimed to analyze the association between parental occupation, family income, and the availability of healthy latrines with the incidence of stunting among children under five in the working area of Batu Bua Primary Health Center, Murung Raya Regency, in 2025. This study employed an analytical observational design with a cross- sectional approach. The study population consisted of all children under five in the working area of Batu Bua Primary Health Center, with a total sample of 71 children selected using purposive sampling. Data were collected through interviews using questionnaires and anthropometric measurements based on height-for-age (H/A) indicators. Data analysis included univariate and bivariate analyses using the Chi- Square test and Fisher’s Exact Test at a 95% confidence level. The results showed that most children were in the 24–59 months age group and were male. Bivariate analysis demonstrated a significant association between parental occupation and the incidence of stunting. Family income and the availability of healthy latrines were not significantly associated with stunting among children under five in the working area of Batu Bua Primary Health Center, Murung Raya Regency, in 2025. This study concludes that parental occupation is associated with the incidence of stunting among children under five. Family income and the availability of healthy latrines were not significantly associated with stunting. Therefore, stunting prevention efforts should focus on improving family socio-economic conditions, strengthening nutrition education, and implementing integrated health interventions.